Angiotensin Converting Enzyme and Dipeptidyl Peptidase-IV Inhibitory, and Antioxidant Activities of a Blue Mussel (Mytilus edulis) Meat Protein Extract and Its Hydrolysates. Issue 8 (16th November 2016) - Neves, Adriana C.; Harnedy, Pádraigín A.; FitzGerald, Richard J.
ABSTRACT: Protein extracted from mussel processing coproducts was hydrolyzed with four different food-grade enzyme preparations and assessed for angiotensin converting enzyme (ACE) and dipeptidyl peptidase-IV (DPP-IV) inhibitory and oxygen radical antioxidant capacity (ORAC) activities. All hydrolysates tested showed higher activity than the intact protein. ACE and DPP-IV IC50 values in the range 1.13–3.34 and 0.33–2.43 mg mL −1, respectively, and ORAC values in the range 66.26–121.56 µmol trolox equivalents g –1 were obtained. These results suggest that some of the mussel meat protein hydrolysates may have potential as functional food ingredients for the management of diseases such as type II diabetes and hypertension.